Distance education under duress: a case study of exchange students' experience with online learning during the COVID-19 pandemic in the Republic of Korea. (31st January 2022) - Stewart, William H.; Lowenthal, Patrick R.
Abstract: COVID-19 caused universities around the world to transition overnight to some type of remote learning or online format. The way this occurred, though necessary, was a departure from the standards and norms of traditional distance education and was a drastic change for the majority of faculty and students who had no prior experience with remote, blended, or online learning. This case study was conducted in the Republic of Korea with 15 international exchange students who found themselves forced to take distance education courses on an empty campus during the COVID-19 pandemic. Themes of isolation and loneliness, diverse learning experiences, little-to-no social interaction, teaching, cognitive, or social presence emerged from the interviews. In this paper, we discuss our findings and the implications for future research and practice.